Mathematical programming methods for microgrid design and operations: a survey on deterministic and stochastic approaches - Wang, Guanglei; Hijazi, Hassan (Computational optimization and applications, 2018)
Planning and operating a power grid is a nontrivial exercise due to conflicting objectives, nonlinear constraints and uncertainties at multiple decision levels. Considerable research work has been dedicated to independently solve different aspects of the overall problem. This survey provides a detailed review of state-of-the-art techniques in mathematical optimization trying to address challenges in this area. We also provide a set of open problems and research perspectives.